2005
DOI: 10.1016/j.visres.2004.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the processing of gaze direction and facial expression

Abstract: In this article, we explored the relationship between the processing of facial expression and the processing of gaze direction. In Experiment 1, participants were unable to ignore gaze while classifying expression-or to ignore expression while classifying gaze. This suggests that the processing of expression and the processing of gaze are interdependent. In Experiment 2, the faces were inverted to isolate configural from part-based contributions to this interdependence. Inversion had a striking effect on expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
96
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 14 publications
21
96
1
Order By: Relevance
“…This asymmetry was most likely because of the relative discriminability of gaze and emotion, because our reaction time analysis indicated that participants were faster at making emotion judgments than gaze judgments. Comparison of the angry faces used in this experiment and in Ganel et al (2005) by a certified FACS coder (R.G.) confirmed that the angry face used in this experiment was more intense than those used in Ganel et al (2005) and strengthens our previous finding that baseline discriminability can have an impact on results (see Appendix).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This asymmetry was most likely because of the relative discriminability of gaze and emotion, because our reaction time analysis indicated that participants were faster at making emotion judgments than gaze judgments. Comparison of the angry faces used in this experiment and in Ganel et al (2005) by a certified FACS coder (R.G.) confirmed that the angry face used in this experiment was more intense than those used in Ganel et al (2005) and strengthens our previous finding that baseline discriminability can have an impact on results (see Appendix).…”
Section: Discussionsupporting
confidence: 84%
“…However, the conditions under which the two processes interact and the extent and nature of these interactions remain unclear. The goal of the present study was to provide behavioral evidence of gaze and expression interactions using the Garner selective attention paradigm, extending the results of Ganel et al (2005) in three directions.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Cueing stimuli were derived from photographs of one male face displaying happy, fearful, angry or neutral expression, selected from Ekman and Facial expressions of one actor only were presented to prevent unwarranted effects of variations in identity of face stimuli (Ganel et al 2005). Hair and non-facial areas were removed so that only the central face area was visible.…”
Section: Stimuli and Pr Ocedur Ementioning
confidence: 99%
“…The social dimensions of eye movements are again attracting the interests of researchers (Ganel et al 2005). It is clear that the experimental study of faces has a rich history on which to draw.…”
mentioning
confidence: 99%